Evaluation of fluorescence images acquired from oligonucleotide libraries - Cysewska-Sobusiak, Anna; Bołtrukiewicz, Michał; Parzych, Joanna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
By using a given DNA sequence, labeled with an organic dye, fluorescence may be induced as the effect of the hybridization of the sequence with complementary oligonucleotides located in a so-called library. The analysis consists in the detection of lighting points, in which the hybridization occurred. Each image of the created matrix corresponds to the optical response of a given oligonucleotide included in the investigated sequence spectrum. A novel approach to modeling of images obtained from a virtual oligonucleotide library and detected by a CCD camera is presented. Tests to determine optimum algorithms of the oligonucleotide library detection were carried out in the form of a computer simulation. Analyzed recorded images do not represent the actual illuminated oligonucleotide library, but were obtained by simulation in an identical way and by means of the same set of instruments. As a result, it was proven how to obtain correct detection depending on a mutual location of a given oligonucleotide library and the CCD matrix.
Optica Applicata, Vol. 38, 2008, nr 2, s. 375-386
Keywords: optyka; CCD matrix; DNA; fluorescence; image analysis